Parenting Needs Among Mothers of Young Children During Military Deployment. Issue 4 (26th May 2018) - Trautmann, Jennifer; Ho, Grace W.K.; Gross, Deborah
Abstract: Purpose: To examine perceptions of what mothers of young children (birth to 5 years old) need to be a "good parent" while their military spouse is deployed. Design: Q methodology was used to uncover different views on military spouses' parenting needs. Methods: In Phase 1, 18 statements related to military spouses' parenting needs were elicited based on review of existing literature and seven supplementary qualitative interviews. In Phase 2, 143 military‐connected mothers completed an anonymous online Q‐sort to rank the importance of the 17 statements from least to most important for being a good parent during deployment. Written comments explaining rankings were also collected. Findings: Across respondents, the most important needs during deployment were making sure their children were happy and healthy, keeping themselves and their children connected with the deployed parent, and being financially stable. Three unique views were uncovered, which differed by mothers' reliance on their family versus the military community for support, and the importance of self‐care. Conclusions: Results highlighted the extent to which mothers of young children enter "survival mode" during their spouse's deployment, and differences were found in what was most important for being a good parent during this stressful period. Clinical Relevance: Findings underscore the complexity of creating programs to support military parents whose different backgrounds, experiences, and expectations are likely to affect service uptake and benefit.